Bcl11b—A Critical Neurodevelopmental Transcription Factor—Roles in Health and Disease - Lennon, Matthew J.; Jones, Simon P.; Lovelace, Michael D.; Guillemin, Gilles J.; Brew, Bruce J. (Frontiers in Cellular Neuroscience, 2017)
B cell leukaemia 11b (Bcl11b) is a zinc finger protein transcription factor with a multiplicity of functions. It works as both a genetic suppressor and activator, acting directly, attaching to promoter regions, as well as indirectly, attaching to promoter-bound transcription factors. Bcl11b is a fundamental transcription factor in foetal development, with important roles for the differentiation and development of various neuronal subtypes in the central nervous system (CNS). It has been used as a specific marker of layer V subcerebral projection neurons as well as striatal interneurons. Bcl11b also has critical developmental functions in the immune, integumentary and cardiac systems, to the extent that Bcl11b knockout mice are incompatible with extra-uterine life. Bcl11b has been implicated in a number of disease states including Huntington’s disease, Alzheimer’s disease, HIV and T-Cell malignancy, amongst others. Bcl11b is a fascinating protein whose critical roles in the CNS and other parts of the body are yet to be fully explicated. This review summarizes the current literature on Bcl11b and its functions in development, health and disease as well as future directions for research.